The resilience of the Spanish monarchy, 1665-1700 - Storrs, Christopher (Oxford University Press, 2006)
Christopher Storrs presents an analysis of why Spain and its empire survived during the reign of the last Spainish Hapsburg. He argues it was not wholly due to the aid of allies but also because the state and society were clearly committed to the retention of empire.